2022
DOI: 10.1186/s12864-021-08273-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of microRNAs and expression profiles during rhizome development in ginger (Zingiber officinale Roscoe)

Abstract: Background MicroRNAs (miRNAs) are endogenous, non-coding small functional RNAs that govern the post-transcriptional regulatory system of gene expression and control the growth and development of plants. Ginger is an herb that is well-known for its flavor and medicinal properties. The genes involved in ginger rhizome development and secondary metabolism have been discovered, but the genome-wide identification of miRNAs and their overall expression profiles and targets during ginger rhizome devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…This observation reinforces the reliability of our results and aligns with previous findings emphasizing the pivotal role of uracil at the start of the mature miRNA in governing miRNA-mediated regulatory mechanisms. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…This observation reinforces the reliability of our results and aligns with previous findings emphasizing the pivotal role of uracil at the start of the mature miRNA in governing miRNA-mediated regulatory mechanisms. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…Comparative transcriptomic studies of ginger and mango ginger are also reported to have 13 miRNA families with >300 target regions that are involved in cell signaling, reproduction, metabolism, and bacterial wilt stress ( Snigdha and Prasath, 2021 ). Another study also reported 104 new miRNAs, and 28 differentially expressed miRNA families, along with their targeted genes involved in rhizome development ( Xing et al, 2022 ). In the case of garlic, by EST approach, six miRNA families are reported to regulate stress response ( Panda et al, 2014 ).…”
Section: Noncoding Rnas: Switch Guiding Switch Resourcesmentioning
confidence: 99%
“…Ante ello, es indispensable buscar alternativas que disminuyan la metanogénesis ruminal, y que a su vez, no afecten el bienestar de los animales, ni representen riesgo a la salud de los consumidores ante la posibilidad de residuos en la carne o leche. Bajo este contexto, una alternativa es el uso de aditivos de origen vegetal como el jengibre (Zingiber officinale Roscoe), el cual es fuente de diferentes metabolitos secundarios, como compuestos fenólicos y terpenos (Mao et al 2019), y de micro RNAs (Xing et al 2022), mismos que han mostrado capacidad de modular las poblaciones de la microbiota intestinal (Teng et al 2018, Wang et al 2021.…”
Section: Introductionunclassified